Importance of Acute Anterior Angulation in Double Aortic Arch Needing Attention at Primary Surgery - Beeman, Arun; Ramaswamy, Madhavan; Srinivasan, Yadav; Rudrappa, Siddartha; Christov, Georgi; Marek, Jan; Derrick, Graham; Muthialu, Nagarajan (Frontiers in Cardiovascular Medicine, 2022)
Background Vascular rings are rare congenital abnormalities of aortic arch. There are many embryological variants including double aortic arch. In symptomatic children, division of ring and release of airway structures may be sufficient. Persistence of symptoms can be related to anterior angle formed between two arches. The aim of this study is to evaluate the clinical efficacy in improving symptoms, on changing this angle at primary surgery. Methods All children who had surgery for doublé aortic arch between 2005 and 2020, were studied. Relevant factors were analyzed for persistent symptoms including anatomical substrates and surgical details. Results 87 out of 224 children had surgery for double aortic arch. At presentation, airway symptoms (n = 74/87) were more common than esophageal symptoms (n = 27/87). Early onset symptoms within 1 year seen in 49 children. In addition to division of one arch, surgical steps also included realigning the anterior left arch, thereby eliminating acute angle, in 36 children (after 2014). After surgery, symptom relief within twelve months following surgery was seen in 64% of children (56 out of 87) but in 27 out of 36 children (75%) with additional surgical modification, as against 29 out of 51 (57%) in those with division of arch. Symptoms persisted beyond one year needing reintervention in 8 children. Conclusion Anterior arch angulation plays an important role in double aortic arch by causing a ‘nutcracker’ phenomenon. Repair in double aortic arch should consider this aspect and include modification of surgical steps by realigning the corresponding aortic arch branches and an anterior pexy in selected cases.